Optimizing the Role of Community-Based Enterprises to Improve Performance and Competitiveness in Indonesia - Nihayah, Dyah Maya; Pujiati, Amin; Rahman, Yosi Aulia; Nihayah, Annis Nurfitriana; Nursaidah, Nursaidah; Damayanti, Anggita; Ridzuan, Abdul Rahim (Muhammadiyah University Press, 2024)
This study aims to identify the characteristics and roles of the village-owned enterprises (BUMDES) model and determine the appropriate development strategy to improve performance and competitiveness. This research is a qualitative study with a case study approach. Data were taken from key persons the director of BUMDES, village officials, and the community as BUMDES partners in Semarang Regency. Data were analyzed using Atlas.ti and Analytical Networking Process (ANP) methods. The results show that BUMDES in Semarang Regency leads to the community-based enterprises (CBE) model than social enterprises because some of the characteristics they have to include the purpose of establishing BUMDES is to contribute to the village economy through the village income (PADes), improving the welfare of rural communities; BUMDES strategy to gain profits, and have strong social capital. Strategies to improve attractive marketing techniques and increase competence through joint training and mentoring are top priorities to improve performance and competitiveness. The limitation of the study is the sample should include the differentiated BUMDES based on village typology so that models and behavior can be identified according to their respective roots.